Photoswitchable supramolecular catalysis by interparticle host-guest competitive binding - Zhu, Liangliang (2013)
On and off: Ester hydrolysis catalyzed by a ZnII-coordinated β-cyclodextrin dimer can be switched on and off using light in the presence of gold nanoparticles with azobenzene units attatched to their surfaces. Under visible light, the azobenzene units are trans and bind tightly to the dimer, thus leading to reduced catalysis. Under UV light, the azobenzene units are cis and bind loosely to the dimer, thus allowing substrates to bind and hydrolysis to occur.